Prinsip Keadilan Dalam Syariat Islam: Antara Kewajiban Berlaku Adil Dan Larangan Dzalim - Diva Kurnia Dwi Salsabila; Nanda Fitriyahb; Ahsin Haris Ulinnuha; Muh Zamroni (CV. ITTC INDONESIA, 2025)
Justice is a fundamental principle in Islamic law (Sharia) that serves as the foundation for all aspects of life, both individual and social. Islamic teachings emphasize the obligation for every Muslim to act justly in speech, behavior, and decision-making, while strictly prohibiting all forms of injustice (zulm). This study aims to examine the concept of justice from an Islamic perspective and highlight the close relationship between the command to uphold justice and the prohibition against wrongdoing. The method used is library research with a qualitative approach, analyzing primary sources such as the Qur’an, Hadith, and the works of classical and contemporary scholars. The findings indicate that justice in Islam is universal and applies not only to fellow Muslims but to all of humanity. The prohibition of injustice serves as a safeguard for individual and social rights to establish a harmonious society.